Niko's Nature : the Life of Niko Tinbergen and His Science of Animal Behaviour. - Kruuk, Hans (Oxford University Press, Incorporated, 2004)
As a naturalist, Niko Tinbergen was a giant. He was a complex and interesting character, well connected to other science luminaries such as Desmond Morris and Richard Dawkins. His pioneering work in ethology won him a Nobel prize, co-authored with Konrad Lorenz, a one-time Nazi. This fascinating story, beautifully illustrated throughout with photographs and with Tinbergen's own drawings, is written by his biographer and friend, Hans Kruuk, himself a widely-respectedscientist and author.